Kebijakan ‘Physical Distancing’ sebagai Pemicu Kreativitas Merancang Ruang Arsitektur - Meivirina Hanum (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2021)
Covid-19 pandemic has successfully triggered major changes in human behavior, spread suffering physically and psychologically to humans, destroyed the economic order of society, country, and even whole world. In the other side, it also contributed positively, being one of the triggers for creative ideas in designing Architecture. Physical distancing one of ways to prevent the transmission of Covid-19 contributed as ammunition for architects, as a conceptual foundation for designing architectural spaces. How this change in space standards becomes a trigger to explore the source of the architectural concept, considering changes in that area means changes in the proportions of its mass? The purpose of this paper is to provide alternative ideas in exploring the provision of architectural space that meets the health protocol physical distancing has been set by WHO. The method used is descriptive-comparative by referring to the standard of architectural space requirements as well as several related journals and the provisions of physical distancing. The writing will be carried out by setting side by side and comparing between the basic standard of space requirements and the standard provisions of physical distancing. The conclusion of this paper is the birth of new ideas in architectural space design.